Impact of celiac disease on patients with familial Mediterranean fever: a nationwide study based on the Türkiye database - Bozkuş, Rıfat; Güven, Serdar Can; Başer, Salih; Yılmaz Çakmak, Nuray; Satış, Hasan; Gemcioğlu, Emin; Ata, Naim; Birinci, Şuayip (Frontiers in Immunology, 2025)
IntroductionFamilial Mediterranean fever (FMF) and celiac disease (CD) are both immune-mediated disorders that may share overlapping inflammatory mechanisms. This study aimed to evaluate the clinical features, comorbidities, inflammatory markers, and treatment regimens in adult FMF patients with and without concurrent CD.MethodsIn this retrospective, multicenter, nationwide study, data were obtained from the Turkish Ministry of Health’s National Electronic Database (e-Nabız). Diagnoses of FMF and CD were determined using ICD-10 codes and validated through clinical, serological, and histopathological records. A control group of FMF patients without CD was matched by age and sex. Demographic characteristics, comorbid conditions, medication use, emergency visits, surgical history, and serum amyloid A levels were analyzed.ResultsOut of 184,786 adult FMF patients, 523 had coexisting CD and were compared with 523 matched FMF controls. Joint involvement rates were similar (p = 0.063), while comorbidities such as thyroid dysfunction, diabetes, depression (all p < 0.001), migraine (p = 0.009), and fibromyalgia (p= 0.003) were more prevalent in FMF–CD patients. Emergency visits for abdominal pain (p < 0.001) and peritonitis (p = 0.005) were significantly higher. Use of colchicine (compressed form), methotrexate, hydroxychloroquine, and methylprednisolone was also elevated (all p < 0.05).ConclusionCoexisting CD in FMF patients is associated with a higher comorbidity burden, increased indirect inflammation, and greater use of immunomodulatory drugs. These findings suggest a more complex clinical profile but are limited by the absence of standardized disease activity metrics. Prospective studies using validated indices are needed for clearer insight and tailored management.